2022
DOI: 10.3389/fcell.2022.894305
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Regulation of Non-Coding RNAs by Resveratrol: Molecular Insights and Therapeutic Applications

Abstract: There have been significant advances, particularly over the last 20 years, in the identification of non-coding RNAs (ncRNAs) and their pathophysiological role in a wide range of disease states, particularly cancer and other chronic conditions characterized by excess inflammation and oxidative stress such as atherosclerosis, diabetes, obesity, multiple sclerosis, osteoporosis, liver and lung fibrosis. Such discoveries have potential therapeutic implications as a better understanding of the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…Notably, resveratrol has been found to affect the expression of several genes including cytokine coding genes, caspases, matrix metalloproteinases, adhesion molecules, and growth factors [ 101 ]. In addition to the mentioned protein coding genes, evidence from in vitro and in vivo assays has shown the direct effects of resveratrol on several non-coding genes and possible implication of these transcripts in the therapeutic effects of resveratrol [ 107 ]. Moreover, it can modulate the activity of several signaling pathways such as PI3K/AKT, Wnt, NF-κB, and Notch pathways [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, resveratrol has been found to affect the expression of several genes including cytokine coding genes, caspases, matrix metalloproteinases, adhesion molecules, and growth factors [ 101 ]. In addition to the mentioned protein coding genes, evidence from in vitro and in vivo assays has shown the direct effects of resveratrol on several non-coding genes and possible implication of these transcripts in the therapeutic effects of resveratrol [ 107 ]. Moreover, it can modulate the activity of several signaling pathways such as PI3K/AKT, Wnt, NF-κB, and Notch pathways [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is a polyphenolic phytoalexin derived from many plants such as grapes; groundnut, pine, and vine which revealed anti-cancer effects ( Rauf et al, 2018 ). There have been several research demonstrating the regulation of ncRNAs by resveratrol ( Giordo et al, 2022 ). It inhibits breast cancer cell proliferation by inducing the expression of tumor suppressor miRNAs (miR-34a, miR-424, and miR-503) through the p53 pathway ( Otsuka et al, 2018 ) and lncRNA LINC00978 ( Deng et al, 2016 ).…”
Section: Natural Products Involved In Oxidative Stress and Inflammati...mentioning
confidence: 99%
“…Yan et al (2015), AlAameri et al (2017),Beaver et al (2017),, Palmieri et al (2017,Saghafi et al (2019),Chen et al (2021a),Chen et al (2021b),Irshad and Husain (2021),Kalhori et al (2021),Ma et al (2021),Mishra et al (2021),Ruiz-Manriquez et al (2021),Cesmeli et al (2022),Giordo et al (2022), lncRNA sONE, MALAT 1 Bladé et al (2013), Mishra et al (2019), Ren et al (2020), Ramanujam et al (2021), Elham et al…”
mentioning
confidence: 99%
“…19,[291][292][293][294] It is appropriate to consider polyphenols, such as those found in green tea and red grapes, as future therapeutics due to their broad range of biological functions, such as antioxidant, free radical scavenging, anti-inflammatory, and metal chelating effects. [295][296][297][298][299][300][301][302] Natural flavonoids have been demonstrated in recent studies to alter the action of the proteasome, a multi-enzyme, multi-catalytic complex found in the cytoplasm and nucleus of all eukaryotic cells. The proteasome controls various biological processes, including cell cycle regulation, apoptosis, and the degradation of oxidative, unfolded, and misfolded proteins, as well as antigen presentation.…”
Section: Flavonoid Phytochemicalsmentioning
confidence: 99%
“…Modern nutritional investigations have demonstrated the beneficial effects of polyphenolic antioxidants, found in fruits, vegetables, and their juices, in preventing and treating a broad variety of diseases, including cancer 19,291–294 . It is appropriate to consider polyphenols, such as those found in green tea and red grapes, as future therapeutics due to their broad range of biological functions, such as antioxidant, free radical scavenging, anti‐inflammatory, and metal chelating effects 295–302 . Natural flavonoids have been demonstrated in recent studies to alter the action of the proteasome, a multi‐enzyme, multi‐catalytic complex found in the cytoplasm and nucleus of all eukaryotic cells.…”
Section: The Mechanistic Role Of Phytochemicals Targeting Ups In Cancermentioning
confidence: 99%